Redes de Dos Puertos - Arriola-Valverde, Sergio; Coto-Cortés, Aníbal (My University, 2017)
La unidad contiene todos los subtemas a tratar a lo largo de 16 semanas de curso. Se divide en 6 partes que contienen ejercicios, animaciones, imágenes, teoría y lecturas recomendadas. Se estudian los conceptos de redes de uno y dos puertos, parámetros de impedancia, admitancia y red equivalente, parámetros híbridos y la interconexión entre múltiples redes.

This unit has all the necessary sub-topics over the 16 weeks' course. It is divided into 9 parts containing proposed exercises, animations, images, theory and recommended readings. The concepts of single and two-port networks, impedance, admittance and equivalent network parameters, hybrid parameters and the interconnection between multiple networks are studied.
Keywords: Redes; Parámetros; Híbridos; Interconexión; Circuitos eléctricos; Nets; Parameters; Hybrids; Interconnection; Electrical circuits